Prime Minister Decree No. 1486 Of The Year 2016 On The Re-organization Of the Ministry Of Investment = قرار رئيس مجلس الوزراء رقم 1486 لسنة 2016 بإعادة تنظيم وزارة الاستثمار - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic